Breaking the Pendulum: A suggestive agonist reading about penalty (Delito y Sociedad, 2019)
Breaking the Pendulum: The Long Struggle Over Criminal Justice, one of the most relevant books of the last years in the study of punishment and society, was published in 2017. In this article we present a general review of the book by describing both its principal theoretical contributions to the discipline and the consequences that its methodological framework could have on the exploration of Latin American penality. Specifically, we highlight the authors’ critiques to the epochal descriptions in the penal field and their links with the regional reality. In addition, we delve into some theoretical lessons that can be drawn from the book, bysettinga dialogue with a number of the last key criminological and socio-legal analyses on penality.
Keywords: penality; penal field; penal struggles